Adaptation of Mapiko elements to educative theatre - De Abreu, Evaristo (My University, 2013)
Mapiko is a dance that is practiced in northern Mozambique. This dance is usually associated with the rites of passage from youth to adulthood. Over time Mapiko has undergone several mutations according to the social, cultural and economic changes in the community. The adaptation described in this paper came out of many years of theatrical practice and research into the traditional values of Mozambique. The aim was o produce a theatre experience which has cultural elements that could be recognized by Mozambicans and which would link them to modern, contemporary and perhaps post-modern theatre techniques. the resulting play made use of elements of Mapiko dance, playback theatre and the text "We killed Mangy-Dog" written by Luis Bernardo Honwana. [Abbreviated Abstract. Open document to view full version]
A research report presented to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Masters Degree in Arts, February 2013
Keywords: Theater--Mozambique; Theater and society--Mozambique; Mapiko (Dance drama); Makonde (African people)--Rites and ceremonies; Improvisation (Acting); Playback theater; Drama--Therapeutic use; Mozambique--Social life and customs; Africa, Portuguese-speaking--Social life and customs